Technology at the margins how IT meets the needs of emerging markets - Chutani, Sailesh, 1964- (Microsoft executive leadership series ;, 2011)
"Remain competitive by offering more accessible, affordable, and relevant information technologies that meet mass-market needs Technology at the Margins demonstrates that by making IT more accessible, affordable, and relevant, new mass markets can be opened. Based on solid insights generated in key areas of health, education, finance and the environment, the book offers practical recommendations and insights from world leaders, innovators, practitioners and new users of emergent technologies. Offers recommendations on how companies can ensure their own competitiveness by offering more accessible, affordable, and relevant information technologies to support mass market needs Suggests practical recommendations and insights from world leaders, innovators, practitioners and new users of emergent technologies Challenges businesses to rethink their uses of existing technologies Technology at the Margins will be of interest to decision makers in the private, public and nonprofit sectors who are interested in opportunities offered by IT in meeting the needs of those at the base of the worlds economic pyramid."--Provided by publisher.